Finding meaning in the text: The process of interpretation in text-based divination - Zeitlyn, D (Royal Anthropological Institute, 2001)
Some systems of divination are used to select particular sections of text, which are typically arcane and erudite, in which lies the answer to the particular, pressing problems of the client. Celebrated examples of such systems are the Chinese 1 Ching and the Yoruba Ifa. Werbner's work on Kalanga and Tswapong divination provides a case-study of the detailed praxis in such systems. Diviners have 3 multiple role when a divination technique selects a text. At each consultation they must satisfy themselves, their client, and their audience that they have followed the correct procedures to select the text. A second stage follows. The client has a particular question and the selected text was not composed as a specific answer to it. Interpretation is required to satisfy the client that the question has been answered. The diviner thus plays the role of indigenous critic, a role both similar to and different from that of literary critics in the Western tradition. The concept of 'dialogic' used by Barber in her analysis of Yoruba praise poetry is taken to illustrate similarities and differences between diviner and critic.